2002
DOI: 10.1074/jbc.m110885200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate 1 Translocation to the Nucleus by the Human JC Virus T-antigen

Abstract: Insulin receptor substrate 1 (IRS-1) is the major signaling molecule for the insulin and insulin-like growth factor I receptors, which transduces both metabolic and growth-promoting signals, and has transforming properties when overexpressed in the cells. Here we show that IRS-1 is translocated to the nucleus in the presence of the early viral protein-T-antigen of the human polyomavirus JC. Nuclear IRS-1 was detected in T-antigenpositive cell lines and in T-antigen-positive biopsies from patients diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
3
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(141 citation statements)
references
References 42 publications
(66 reference statements)
6
128
3
4
Order By: Relevance
“…Lower panel: The abundance of pS2 and 36B4 mRNAs in COS-7 cells transfected with different plasmids was detected by RT-PCR, as described in Materials and methods Nuclear IRS-1/ERa interactions C Morelli et al tion of IRS-1 is blocked with ICI and does not occur in ERa-negative cells; (3) nuclear IRS-1 interacts with ERa; (4) nuclear IRS-1 is corecruited with ERa to the ERE-containing pS2 promoter; and (5) the presence of IRS-1 decreases ERa transcription at ERE promoters. Nuclear localization of IRS-1 has recently been described in different cellular systems (Lassak et al, 2002;Prisco et al, 2002;Sun et al, 2003;Tu et al, 2002;Sciacca et al, 2003). The mechanism by which IRS-1 enters cell nucleus is still not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower panel: The abundance of pS2 and 36B4 mRNAs in COS-7 cells transfected with different plasmids was detected by RT-PCR, as described in Materials and methods Nuclear IRS-1/ERa interactions C Morelli et al tion of IRS-1 is blocked with ICI and does not occur in ERa-negative cells; (3) nuclear IRS-1 interacts with ERa; (4) nuclear IRS-1 is corecruited with ERa to the ERE-containing pS2 promoter; and (5) the presence of IRS-1 decreases ERa transcription at ERE promoters. Nuclear localization of IRS-1 has recently been described in different cellular systems (Lassak et al, 2002;Prisco et al, 2002;Sun et al, 2003;Tu et al, 2002;Sciacca et al, 2003). The mechanism by which IRS-1 enters cell nucleus is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its conventional role as a cytoplasmic signaling molecule, IRS-1 appears to function in the nuclear compartment. Several rigorously controlled studies demonstrated that nuclear IRS-1 can be found in cells transformed by oncogenic proteins, for example, T antigens of the JCV (Lassak et al, 2002) and SV40 viruses, and v-src (Tu et al, 2002). Nuclear translocation of IRS-1 has also been described in mouse embryo fibroblasts stimulated with IGF-I (Tu et al, 2002;Sun et al, 2003), 32D murine cells (Sciacca et al, 2003), osteoblasts (Seol and Kim, 2003), and hepatocytes (Boylan and Gruppuso, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IRS-1 is translocated to the nuclei in cells that express the SV40T antigen or its human equivalent (Lassak et al, 2002). However, T antigen cannot transform MEFs unless IRS-1 is tyrosyl phosphorylated (DeAngelis et al, 2006).…”
Section: Status Of Nuclear Irs-1 Phosphorylation In R12 Cellsmentioning
confidence: 99%
“…More recently, IRS-1 has been found in nuclei and nucleoli of cells, either after stimulation with IGF-1 (Tu et al, 2002), or in association with the T antigens of SV40 or its human equivalent (Lassak et al, 2002;Prisco et al, 2002). Nuclear IRS-1 binds the upstream binding factor 1 (UBF1), one of the proteins that regulate RNA polymerase I activity (Tu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%